Geographical distribution of SARS‐CoV‐2 amino acids mutations and the concomitant evolution of seven distinct clades in non‐human hosts. (25th May 2022) - Magateshvaren Saras, Murali Aadhitya; Patro, L. Ponoop Prasad; Uttamrao, Patil Pranita; Rathinavelan, Thenmalarchelvi
Abstract: Since its first emergence in December 2019, the world has witnessed the eruption of mutations in the SARS‐CoV‐2 genome that have led to increased viral transmissibility and pathogenicity due to sustained local viral transmission. Zooanthroponotic and zoonotic transmissions have further raised concerns as they could result in the emergence of viral variants with a novel antigenicity and transmissibility that could jeopardize the vaccine efficacy. To understand the viral evolution during such transmissions, 1016 whole‐genome sequences (deposited in GISAID as of March 7, 2022) (from 18 countries) corresponding to mink, cat, deer, dog, hyena, tiger, lion, gorilla, Syrian hamster, leopard cat, fishing cat, bear cat, coati, ferret, snow leopard and green monkey have been analysed here. Intriguingly, phyloproteome analysis indicate that Nsp2:R218C, Nsp2:D268‐(deletion), Spike:D614G, Nsp12:P323L, Nsp2:A192V, ORF3a protein:Q57H, N protein:R203K and N protein:G204R/L, Spike:A222V, ORF10 protein:V30L and N protein:A220V are moderate or high recurring and clade decisive mutations, leading to 6 primary clades during the early stage of pandemic. Most interestingly, the human evolved delta variant having a combination of 26 (clade decisive) mutations defines the seventh clade and transmits to non‐human hosts across the globe without exhibiting any country‐specific mutation(s). Nonetheless, Spike:D614G and Nsp12:P323L together with (i)N protein:R203K, N protein:G204R/L, Spike:V70‐, Spike:H69‐, Nsp12:T739I, and Nsp1:M85‐, (ii)Nsp2:A192V, Nsp3:D178Y, (iii)Nsp2:T85I, N protein:P67S and ORF3a protein:Q57H and (iv)Spike:A222V, ORF10 protein:V30L, N protein:A220V and Spike:F486I are specific to Denmark, Netherlands, USA and Latvia respectively and, (v)Nsp2:D268‐ and Nsp13:R292C that are devoid of Spike:D614G and Nsp12:P323L is specific to Netherlands. SARS‐CoV‐2 variants consisting of these mutations are also seen in the human SARS‐CoV‐2 sequences from the same country. Independent country‐specific SARS‐CoV‐2 variant evolution further indicates distinct epidemiological dynamics during zooanthroponotic and zoonotic transmissions. Thus, the results presented here indicate the need for the surveillance of viral evolution in non‐human hosts also during the future pandemic.